Systemic inflammatory indices and mortality risk in heart failure: a retrospective cohort study - Arın, Can Baba; Dahir, Osman Farah; Adan, Ahmed Shafie; Abdi, Ishak Ahmed; Karataş, Mesut (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHeart failure (HF) remains a major cause of morbidity and mortality worldwide. Inflammation, malnutrition, and immune dysregulation contribute to adverse outcomes. The CALLY score—a composite index of C-reactive protein (CRP), albumin, and lymphocyte count—has emerged as an integrative biomarker of systemic inflammation, nutritional status, and immune function. This study evaluated the prognostic significance of the CALLY score in predicting in-hospital mortality among patients hospitalized with HF.MethodsThis retrospective observational study included 220 adult patients admitted with HF between January 2022 and December 2024. Patients were stratified into tertiles based on their admission CALLY score. The primary outcome was in-hospital mortality. Cox proportional hazards modeling and restricted cubic spline (RCS) regression were applied to identify predictors of mortality and assess nonlinear associations. Kaplan–Meier analysis evaluated survival differences by hospital stay duration.ResultsAmong 220 patients, 26 (11.8%) died in-hospital. Non-survivors had lower CALLY scores (1.27 ± 0.72 vs. 1.71 ± 0.60; p < 0.001). In multivariable Cox regression, age (HR: 1.105; 95% CI: 1.031–1.202; p = 0.004) and the CALLY score (HR: 0.495; 95% CI: 0.281–1.010; p = 0.047) were associated with mortality. RCS showed an inverse, nonlinear association between CALLY and mortality risk.ConclusionThe CALLY score shows a borderline independent association with in-hospital mortality and may aid early risk stratification. Prospective validation is warranted.